Sterol Carrier Protein Inhibition-Based Control of Mosquito Vectors: Current Knowledge and Future Perspectives - Hirunika Perera; Tharaka Wijerathna (Canadian Journal of Infectious Diseases and Medical Microbiology)
Cholesterol is one of the most vital compounds for animals as it is involved in various biological processes and acts as the structural material in the body. However, insects do not have some of the essential enzymes in the cholesterol biosynthesis pathway and this makes them dependent on dietary cholesterol. Thus, the blocking of cholesterol uptake may have detrimental effects on the survival of the insect. Utilizing this character, certain phytochemicals can be used to inhibit mosquito sterol carrier protein-2 (AeSCP-2) activity via competitive binding and proven to have effective insecticidal activities against disease-transmitting mosquitoes and other insect vectors. A range of synthetic compounds, phytochemicals, and synthetic analogs of phytochemicals are found to have AeSCP-2 inhibitory activity. Phytochemicals such as alpha-mangostin can be considered as the most promising group of compounds when considering the minimum environmental impact and availability at a low cost. Once the few limitations such as very low persistence in the environment are addressed successfully, these chemicals may be used as an effective tool for controlling mosquitoes and other disease-transmitting vector populations.